Екологічний розподіл водних твердокрилих у біотопах Рівненської області - Гусаковська, Тетяна; Gusakovskaа, Tetayna (Східноєвропейський Національний університет імені Лесі Українки, 2015)
У статті представлено дослідження екологічного розподілу водних твердокрилих у біотопах різних типів водойм. Визначено видовий склад Hydradephaga, які відносяться до чотирьох екологічних груп (реобіонтів, реофілів, помірних реофілів, стагнофілів). Встановлено екологічну структуру популяцій Hydradephaga, що дасть змогу спрогнозувати сукцесійні процеси в екосистемах. The article includes a study of the ecological distribution of aquatic Coleoptera in habitats of different types of water bodies. It hes been devined species composition of Hydradephaga, which belong to four ecological groups (reobiontov, reophylov, relatively moderate reophilov, stagnopilov). The analysis of species composition of aquatic Coleoptera defined botica specialization, changes in the composition of groups and the characteristics of spatial distribution Adephaga. It is shown that the species taxonomically close, usually have similar habitat preferences. The obtained information about the distribution of species of aquatic Adephaga within the West Polesie significantly reinforce and clarify data on the species area of habitats. The establishment of the ecological structure of populations of Hydradephaga will determine the types of biological indicators, as well as to predict the mechanisms succese in ecosistema.
Ecological Distribution of Aquatic Coleoptera in the Biotopes of Rivne Region.
Keywords: колеоптерофауна; реобіонти; реофіли; стагнофіли; coleopteran; coleopteran; reophyl; stagnopil